2018
DOI: 10.1080/21691401.2018.1463232
|View full text |Cite
|
Sign up to set email alerts
|

Surface engineered lipid nanoparticle-mediated site-specific drug delivery system for the treatment of inflammatory bowel disease

Abstract: The major challenge for the treatment of inflammatory bowel disease (IBD) is the incompetence to deliver the drug molecule selectively at the site of inflammation. Taking this into consideration, we proposed development of mannosylated nanostructured lipid carrier system (Mn-NLCs) for active targeting and site-specific delivery of budesonide to the inflamed tissues. The developed Mn-NLCs were characterized for particle size and size distribution, zeta potential, %entrapment efficiency, FTIR and TEM analysis. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…Drug delivery systems superficially modified with related ligands can specifically bind to receptors on inflamed cells, deliver drug into target area and achieve great curative effect. Based on the ligand–receptor interaction, receptor-mediated active targeted drug delivery systems could be a promising therapeutic strategy for IBD, as listed in Table 3 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 .…”
Section: Receptors and Cell Adhesion Molecules For Active Targetingmentioning
confidence: 99%
See 2 more Smart Citations
“…Drug delivery systems superficially modified with related ligands can specifically bind to receptors on inflamed cells, deliver drug into target area and achieve great curative effect. Based on the ligand–receptor interaction, receptor-mediated active targeted drug delivery systems could be a promising therapeutic strategy for IBD, as listed in Table 3 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 .…”
Section: Receptors and Cell Adhesion Molecules For Active Targetingmentioning
confidence: 99%
“… Receptor Ligand Carrier Loading cargo Delivery route Characterization Experimental model Principal finding Ref. Mannose receptor Mannose Nanoparticle: PLGA–PEG Ovalbumin Ex vivo S: 212.0 ± 8.0 Z: −7.0 ± 2.0 Proinflammatory cytokines treated Caco-2 cell, DSS-induced female C57BL/6 mice colitis Mannose modification enhanced the endocytosis by Caco-2 cells and accumulation in inflamed colon 34 Mannose Nanoparticle: TPP/poly (CBA-bPEI)-PEG siTNF-α Ex vivo S:275.00 Z: ‒ Raw264.7 macrophage, DSS-induced male FVB mice colitis Introduction of mannose demonstrated a significant increase in intracellular uptake, gene silencing in vitro and ex vivo 35 Mannose Nanoparticle: lipid phase: Compritol 888 ATO/Labrafac WL 1349/stearylamine/Span 80 aqueous phase: Poloxamer 188/ Polysorbate 80 Budesonide Oral S: 301.7 ± 2.88 Z: +7.51 ± 0.71 Oxazolone-induced Wistar rat colitis Surface conjugation of mannose led to superior effects in reduction of MPO, inflammatory cytokines (TNF- α , IL-1 β ) in vivo 36 Mannose Nanoparticle: trimethyl chitosan Mir-146b Oral S: 213.6 ± 16.6 Z: +28.3 ± 6.3 Bone marrow-derived macrophage, DSS-induced C57BL/6 mice colitis Mannosylated nanoparticles could be efficiently recognized and endocytosized by activated intestine macrophages 37 Mannose Nanoparticle: trimethyl chitosan siTNF-α Oral S: 143.3 ± 1.1 Z: +18.7 ± 0.6 Raw264.7 macrophage, DSS-induced C57BL/6 mice colitis Different densities of mannose on nanoparticle displayed different effects on the intracellular uptake and therapeutic efficacy in vitro and in vivo 38 Macrophage galactose lectin Lactobionic acid Nanoparticle: chitosan-PLGA siTNF-α Oral S: 245.60 ± ...…”
Section: Receptors and Cell Adhesion Molecules For Active Targetingmentioning
confidence: 99%
See 1 more Smart Citation
“…Authors attributed that to larger particle size and un-protonated chitosan at neutral pH leading to reduced interaction with mucin. Sinhmar and coworkers fabricated mannosylated NLCs for active targeting of budesonide to the inflamed bowel tissues ( Sinhmar et al, 2018b ). As the surface of macrophages present at the site of inflammation overexpress C-type lectin receptors which can easily recognize mannose, decoration of mannose group to the NLC surfaces could actively deliver the encapsulated drug to inflamed tissues.…”
Section: Applications Of Nlcsmentioning
confidence: 99%
“…Additionally, fluorescence imaging analysis confirmed that the optimized NPs were capable of enhancing retention in the colon. With the same purpose of preventing early BUD release in the upper GIT, Sinhmar et al [ 135 ] used Eudragit ® S100 to incorporate mannosylated nanostructured lipid carriers, which enabled the active targeting of BUD to the inflamed tissues. The active targeting relies on the fact that mannose receptors [175-kDa transmembrane protein of the C-type lectin family (CLR)] are exclusively overexpressed on the surface of pro-inflammatory macrophages.…”
Section: Benefits Of a Nanomedicine-based Therapy For Ibdmentioning
confidence: 99%